A MANUFACTURING INDUSTRY FRAMEWORK THAT HAS IMPLICATIONS FOR THE LEAN ACCOUNTING - Sitoresmi, Mumpuni Wahyudiarti; Eksandy, Arry (Universitas Pamulang, 2018)
This study aimed to examine the factors that affect application of lean accounting at Astra International, Tbk Group companies.This study used sample of Astra International, Tbk group companies that was selected by cluster random sampling base method. From the results of data obtained Astra Motor Components sub-sector was only sector companies that implemented lean accounting with the observational of 8 others sub-sector.Data analysis techniques used multiple linear regression analysis with IBM SPSS STATISTIC 24 program. The results of this study indicates that Continuous Improvement (CI) and Value Stream Cost (VSC) had positive and Value Stream Cost (VSC) had negative effect to implementation of lean accounting. But Just In Time (JIT) had no effect to implementation of lean accounting.